Kinship Values and Traditions in Dayak Kanayatn Folktales: Cultural Transmission and Social Cohesion - Sesilia Seli; Pricilla Pascadeany Frelians (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
This study investigates the kinship values represented in Dayak Kanayatn folktales and their role in preserving traditions, cultural transmission, and social cohesion. Previous studies have primarily examined Dayak oral traditions from linguistic, literary, and cultural perspectives, while limited attention has been given to the relationship between kinship values and traditional practices portrayed in folktales. This study employed a qualitative descriptive approach using qualitative content analysis within the sociology of literature perspective. The data were drawn from five Dayak Kanayatn folktales and analyzed to identify kinship values embedded in traditional practices. The findings reveal eight major kinship values: deliberation, brotherhood, friendship, harmony, mutual help, courtesy, obedience, and honor. These values are represented in six traditions, namely headhunting, notokng, marriage, circumcision, farming, and traditional medicine. The findings demonstrate that these traditions function as cultural mechanisms through which kinship values are practiced, preserved, and transmitted across generations, thereby reinforcing collective identity, social solidarity, and indigenous knowledge. This study contributes to the sociology of oral literature by showing that Dayak Kanayatn folktales function not only as cultural heritage but also as social institutions that sustain kinship systems, preserve cultural identity, and strengthen community cohesion amid contemporary social change.